Chemical and nutritional characteristics of crackers substituted with Cucurbita pepo L. seed flour - Altıner, Dilek Dülger; Sabuncu, Merve; Şahan, Yasemin (Emirates Journal of Food and Agriculture, 2021)
The aim of the study was determined the suitability of Cucurbita pepo L. (pumpkin) seed flour (PSF) supplement, which is limited for use in the food industry, to increase some chemical and functional properties of crackers. PSFs were used to replace wheat flour in cracker formulation at the levels of 5, 10, 20 and 30%. Particularly, the total dietary fiber, protein and ash content of crackers with PSF increased. The highest increase in mineral contents of crackers were determined in P> K> Mg> Ca> Zn> Fe> Cu. The predominant organic acid of crackers was tartaric acid and the dominant fatty acid was linoleic acid. Crackers prepared with Nevşehir variety PSF yielded better results than other crackers due to their nutritious properties. As a result, with the addition of PSF, a functional food product with health benefits was obtained and a contribution was made to the product range.